FOLFIRI plus cetuximab in patients with liver-limited or non-liver-limited RAS wild-type metastatic colorectal cancer: A retrospective subgroup analysis of the CRYSTAL study. Issue 10 (October 2016) - Köhne, C.-H.; Poston, G.; Folprecht, G.; Ciardiello, F.; Ronga, P.; Beier, F.; Van Cutsem, E.
Abstract: Background: Adding cetuximab to first-line FOLFIRI in the phase 3 CRYSTAL trial significantly improved progression-free survival (PFS), overall survival (OS), and objective response rate (ORR) in patients with KRAS wild-type (wt) or RAS wt metastatic colorectal cancer (mCRC). In this retrospective subgroup analysis of CRYSTAL, we investigated benefit of treatment in patients with KRAS wt or RAS wt tumors according to whether patients had liver-limited disease (LLD) or non-LLD, including assessing the role of cetuximab in downsizing metastases and conversion rates from initially unresectable to resectable disease. Methods: PFS, OS, ORR, and R0 resection rates were analyzed according to treatment arm for the LLD and non-LLD subgroups. Results: Of the 367 patients with RAS wt tumors, 89 (24%) had LLD and 278 (76%) had non-LLD. Within the RAS wt LLD and non-LLD subpopulations, demographic and baseline characteristics were comparable between treatment arms. In patients with RAS wt LLD, adding cetuximab to FOLFIRI significantly improved PFS (hazard ratio [HR][95% CI] = 0.21[0.09–0.49]) and ORR (odds ratio [OR][95% CI] = 8.99[3.17–25.52]), and numerically improved OS (HR[95% CI] = 0.65[0.38–1.10]) and R0 resection rate (OR[95% CI] = 2.68[0.63–11.43]) relative to FOLFIRI alone. In patients with RAS wt non-LLD, adding cetuximab to FOLFIRI significantly improved PFS (HR[95% CI] = 0.65[0.46–0.93]), OS (HR[95% CI] = 0.71[0.54–0.93]), ORR (OR[95% CI] = 2.44[1.49–3.98]), and—numerically—R0 resection rate (OR[95% CI] = 5.94[0.79–44.88]). Similar results were obtained from the KRAS wt population. Conclusions: Adding cetuximab to first-line FOLFIRI appears to improve clinical outcomes and R0 resection rates in KRAS wt and RAS wt mCRC patients with LLD as well as in those with non-LLD.